The Role of Teachers in Innovation in Utilizing Audio Visual Media as a Source of History Learning in High Schools - Isak Suhuneap; La Ode Hasirun; Megiridha Loppies; Muhammad Aqil; Kulyasin Kulyasin (JURNAL PENDIDIKAN IPS, 2024)
The objectives of the study are; 1) to find out how the process of the Teacher's Role in Utilizing Audiovisual Media as a Source of History Learning at SMA Muhammadiyah Jayapura City; 2) To find out the Student Response/Reaction to the Role of Teachers in Utilizing Audiovisual Media in History Learning; 3) To find out the implications of the impact of the Role of Teachers in Utilizing Audiovisual Media as a Source of History Learning at SMA Muhammadiyah Jayapura City. This research method uses descriptive qualitative research. Data sources are obtained from interviews, observations and documentation. Analysis is carried out by reduction, interpretation and drawing conclusions. This study proves that the role of teachers in innovation in utilizing audiovisual media is very important in providing motivation during teaching and learning activities. So that the impact of providing this motivation is the presence of a sense of visual interest and students' pleasure in participating in history learning activities. Thus, it can be understood that motivation is indeed important to be given in the classroom by teachers. This is done so that students have strong motivation in the learning process